In vitro and in vivo synergistic inhibition of Malassezia furfur targeting cell membranes by Rosa rugosa Thunb. and Coptidis Rhizoma extracts - Li, Li; He, Yuanyuan; Zou, Qinghui; Chen, Weiwei; Liu, Yanxia; He, Huifen; Zhang, Jun (Frontiers in Microbiology, 2024)
Background Malassezia furfur (M. furfur) is a prevalent dermatophyte that significantly impairs patients’ quality of life. This study aimed to evaluate the synergistic antifungal effects of combined extracts from Rosa rugosa Thunb. (MG) and Coptidis Rhizoma (HL) against M. furfur, both in vitro and in vivo. Methods High-performance liquid chromatography (HPLC) was used to identify the major active compounds present in MG and HL. The antifungal activity of the combined Meilian extract (ML) was assessed using the checkerboard method and time-kill curves. Microstructural alterations in the fungi were observed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The impact of the extracts on the fungal cell membrane was investigated through propidium iodide staining, protein concentration assays, and ergosterol quantification. Transcriptomic analysis was conducted to elucidate the molecular mechanisms underlying the effects of the extracts. Furthermore, the synergistic antifungal effects of ML were evaluated in a mouse model of seborrheic dermatitis induced by M. furfur. Results The study demonstrated that the combined application of MG and HL significantly affected the integrity of the M. furfur cell membrane and potentially modulated its formation processes. In the M. furfur-induced seborrheic dermatitis model, ML exhibited synergistic antifungal effects and effectively alleviated skin inflammation. These findings provide an important theoretical basis for understanding the antifungal mechanisms of ML and its potential application in dermatological therapy.